Menace of Ragging: Addressing Concerns - Manani, Preeti (Voices of Teachers and Teacher Educators, 2019)
This article is based on a research study on ragging in higher education institutions with special reference to a medical college in Agra. Though the site is specific it shows the inter-sectionalities between social variables such as caste, class, gender, etc. and frequency and nature of ragging. It also highlights different aspects of ragging such as its origins, causes and implications, thereby offering rich insights. A few cases of ragging highlighted by media are also listed. After discussing suggestions to curb it by several committees set up for the same are discussed and limitations pointed out.